2020
DOI: 10.1111/lre.12316
|View full text |Cite
|
Sign up to set email alerts
|

Supporting adaptive capacity of agropastoralists through fish production and marketing: The case of Tendaho Reservoir

Abstract: The present study was conducted to share the experience of promoting fish production and marketing from the Tendaho Reservoir of the Afar region, Ethiopia. The study results indicate the reservoir is serving its purpose, namely to generate gainful employment for the pastoralist youth and to create sustainable livelihoods and sources of income for the pastoralist‐fishermen of the Afar region. Further, the reservoir fish production has improved the nutrition and food security status of children. It also created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In doing so, respondents in the study area are using fishing and fish-related activities as employment opportunities, in the same way as reported elsewhere (Neiland et al, 2000, Welcomme et al, 2010. In Ethiopia, contributions of another reservoir (Tendaho) in the same manner as the result of this study, has been indicated to be a good source of employment for youth, livelihood income for the pastoralists-fishermen of the Afar people, improved nutrition, and food security (Mesay et al, 2019).…”
Section: Discussionmentioning
confidence: 52%
“…In doing so, respondents in the study area are using fishing and fish-related activities as employment opportunities, in the same way as reported elsewhere (Neiland et al, 2000, Welcomme et al, 2010. In Ethiopia, contributions of another reservoir (Tendaho) in the same manner as the result of this study, has been indicated to be a good source of employment for youth, livelihood income for the pastoralists-fishermen of the Afar people, improved nutrition, and food security (Mesay et al, 2019).…”
Section: Discussionmentioning
confidence: 52%
“…The Afar Region is drought prone area and acute child malnutrition is higher than the national average [ 32 ]. On the contrary, that only about 21% of the actual potential of Tendaho Reservoir is currently being exploited by local pastoralists that have settled in the vicinity [ 13 ]. The large majority of pastoralists adjacent to the reservoir normally move with their cattle especially during the dry season.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Ref. [ 13 ] indicated an increase in fish consumption and positive perception to fish as food after fish production begun in Tendaho reservoir. The growing fish demand can be met by integrating capture-based fishery with irrigation farming activities in the region.…”
Section: Introductionmentioning
confidence: 99%